Bolpin (Bola Pintar): Media Interaktif Untuk Meningkatkan Literasi Membaca dan Menulis Pada Pendidikan Anak Usia Dini - Mardiyah Mardiyah; Ahmad Samawi; Sri Wahyuni (Universitas Muhammadiyah Ponorogo, 2026)
Early childhood education (PAUD) is a crucial phase in developing basic literacy, especially reading and writing skills. Literacy needs to be developed early on to support children's readiness to learn. Early childhood learning is based on the principle of learning through play, which emphasizes active involvement and direct experience. However, literacy learning practices in PAUD are still often dominated by conventional approaches that focus on worksheets and books, thereby failing to encourage active participation from children. This situation results in low interest and motivation to learn when learning activities are not supported by engaging media. This study aims to develop Bolpin (Smart Ball) learning media based on an interactive approach and to test its effectiveness in improving the reading and writing skills of early childhood. The study uses the Research and Development (R&D) method with the ADDIE procedure, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were children in group B at RA Miftahul Huda II Sengonagung Purwosari, Pasuruan Regency. Data collection techniques included observation, interviews, and documentation. The feasibility of the media was assessed through validation by subject matter experts and media experts, while its effectiveness was tested using a pre-experimental design with N-Gain analysis based on pretest and posttest results. The results of the study showed that Bolpin media was declared highly valid, with a media expert validation percentage of 93% and a subject matter expert validation percentage of 92%. The application of Bolpin media improved children's reading and writing skills, with an N-Gain value of 0.67 (moderate category). Bolpin media is effective in supporting active and enjoyable literacy learning.